Juridical Overview of the Process of Proving Crimes Committed by Children according to Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (Case Study Decision Number: 9/Pid.Sus- Anak/2019/Pn.Slw) - Dita Mujiaka (Institute Of computer Science (IOCS), 2022)
This study aims to determine the process of proving a crime if the perpetrator is a child according to Law no. 11 of 2012 concerning the Juvenile Criminal Justice System and the obstacles faced in the process of proving criminal acts committed by children. This research was conducted in Tegal, namely the Tegal District Court, the Slawi District Attorney and the Tegal Police, the authors conducted interviews with 1 (one) prosecutor, 1 (one) judge and 1 (one) police investigator, as well as other data obtained through the relevant literature, namely literature, documents and laws and regulations relating to the problem. The data obtained were then processed and analyzed qualitatively-descriptively. Based on the results of research and discussion, the process of proving a crime in a child case is different from proving a general crime (a criminal case for adults). The process of proving a child's crime is regulated in Law no. 11 of 2012 concerning the Juvenile Criminal Justice System starting from the process of investigation, arrest and detention, prosecution to examination in court. In terms of evidence in proving cases of child crimes, it is not specifically regulated in the SPPA Law, therefore it still refers to the Criminal Procedure Code (KUHAP) Article 184. The absence of guidelines for the implementation of diversion practices for law enforcement officers causes the implementation diversion varies depending on the understanding of law enforcement officers and the lack of understanding in the application of the SPPA Law by law enforcement officers.